PERANAN HALUAN NEGARA DALAM MENCAPAI TUJUAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Yuhana, Abdy (LITIGASI, 2024)
The significance of revitalizing the Basic Guidelines of the State Policy (GBHN) through the Contemporary Policy Guidelines (PPHN) serves as a foundation for sustainable development in Indonesia. This revitalization aims to fill the legal void left by the Basic Guidelines of the State Policy (GBHN) and provide clear guidance for sustainable national development. This research employs a normative legal method and qualitative analysis, focusing on the study of legal documents and relevant academic literature. Data collection is conducted through documentation studies that encompass laws, related regulations, and literature addressing the research theme. The Contemporary Policy Guidelines (PPHN) is posited to function as a structured and inclusive framework. Mechanisms such as public consultations, integration of local policies, reinforcement of the legal framework, and effective monitoring and evaluation systems are proposed to ensure that the Contemporary Policy Guidelines (PPHN) serves not merely as a normative document but also as an operational guideline that is responsive to societal needs. Visionary leadership is identified as a key factor in accelerating sustainable development, with an emphasis on inclusive vision and innovation. The revitalization of the Contemporary Policy Guidelines (PPHN) is expected not only to provide a clear direction for national development but also to enhance legal stability and societal welfare. The integration of holistic and sustainable development is deemed essential, involving community participation and coherence between central and regional policies to create lasting positive impacts for society and the environment.